Optimisation of Kaolin bioleaching using surface, chemical and structural studies - Pang, Jun Hao (2024)
Kaolin, a valuable clay mineral used in ceramics, whiteware manufacturing, and refractories, faces challenges due to iron impurities affecting its properties and colouration. Conventional methods for iron removal are not sustainable, necessitating eco-friendly alternatives like bioleaching with Bacillus Cereus. This study focuses on exploring how nutrients, particularly yeast and yeast with glucose solution, impact bioleaching efficiency within 10 days of the experiment. This study investigates the morphological, chemical, and structural alterations of kaolin during bioleaching using Bacillus cereus. By analyzing experimental outcomes, it was determined that a combination of yeast extract and glucose solution serves as the optimal nutrient source for enhancing bioleaching efficiency. Phenanthroline analysis revealed a significant increase in Fe (II) concentration from 1.06 µg/ml on day 0 to 3.78 µg/ml on day 10. Energy-dispersive X-ray spectroscopy (EDS) further demonstrated a bioleaching efficiency of 54.88% in batch 1 and 51.55% in batch 2, surpassing previous studies, likely attributable to the selected nutrient types. Surface analysis via scanning electron microscopy (SEM) indicated heightened crystallinity in the kaolin structure post-bioleaching. Remarkably, the chemical composition and bonds of kaolin remained unaltered, as confirmed by X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). This study successfully achieves its objectives and suggests further laboratory-scale optimization to facilitate scale-up. Future investigations will delve into optimizing nutrient types using various Bacillus species to maximize bioleaching efficiency, thereby contributing to the sustainable utilization of kaolin resources. While the nutrient source can be the catalyst to accelerate the progress, different bacteria will have their optimum condition. To further increase the efficiency, other bacteria types rather than Bacillus species can be investigated because the rate of metabolism rate for each bacteria is different, then the duration of bioleaching is also different.